New Perspectives on the Design of Stilling Basins - Farzin Salmasi; John Abraham (Theory and Applications of Engineering Research Vol. 6, 2024)
In the design of hydraulic structures, the water velocity should be maintained at acceptable levels. The high velocity of water in an earthen channel or a natural river causes erosion of the channel bed and walls, which may cause irreparable damage to the facilities adjacent to the river. Also, in many cases, factors such as the steep slope of the channel floor, the large energy difference between two sections, the free fall of water, or the kinetic energy of the water flow is more than expected. This inevitably requires designing structures to reduce the kinetic energy. Such hydraulic facilities are called energy dissipation structures. Different types of energy dissipaters are available, the most common of which are stilling basins. With stilling basins, the flow energy is depleted by the hydraulic jump and the creation of strong turbulence in the stilling basin. For a better understanding of the energy available in the water velocity at the toe of the spillway, we can refer to the Grand Coulee dam. This dam was built on the Columbia River in America. The designed discharge of the dam spillway is 28,320 m3/s and the upstream and downstream water levels for this discharge are 393.8 and 308.23 m, respectively. If it is assumed that the energy loss on the spillway is insignificant, the energy of the water downstream of the spillway is equal to 23 GW according to the relation E=pgQH, where H is the difference in water level between the upstream and downstream sections. If the energy is not restrained properly, even the best conditioned downstream stone protection will undergo severe erosion. The design and construction of stilling basins downstream of dam spillways are one of the most common methods of water energy control and is the subject of this study.